QUANTITATIVE TRAIT LOCI (QTLs) ANALYSIS OF DROUGHT TOLERANCE AT GERMINATION STAGE IN A WHEAT POPULATION DERIVED FROM SYNTHETIC HEXAPLOID AND OPATA - S. Ashraf; A. Shahzad; F. Karamat; M. Iqbal; G. M. Ali (Journal of Animal and Plant Sciences, 2015)
Drought is a major limiting factor affecting productivity. Wheat is a major crop and staple food in Pakistan. Genetic linkage map construction based on linked DNA markers spanning whole wheat genome and subsequently QTL mapping for drought tolerance is a way forward to enhance breeder’s ability for effective selection. An F8 population derived from the cross of OPATA x SH-349 has been used. An experiment was conducted at germination stage under controlled conditions. The drought was induced by15% PEG nutrient solution in acid washed sand medium. Microsatellite DNA markers data were used for linkage maps construction. Morphological data under drought and non-stressed conditions along with linkage maps data were used for QTL mapping. The results of QTL analysis using single marker analysis showed 14 SSR markers  linked to QTLs for five traits in both drought and control condition. Using simple interval mapping and composite interval mapping 12 QTLs for different traits of interest were found. Implications of found QTLs and linked markers are discussed.
Keywords: Drought; SSR; PCR; QTL mapping; wheat